The Effect of Integrity, Quality of Human Resources, Job Attachment, Organizational Characteristics and Work Targets on the Work Effectiveness of UPTD Pasar Tanjung Enim Employees - Tri Jaya Saputra; Sulbahri Madjir; Darmin Darmin (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
Research with the aim of knowing and analyzing the influence of integrity, quality of human resources, work engagement, organizational characteristics and work targets partially and simultaneously on the work effectiveness of employees of the Tanjung Enim Market Regional Technical Implementation Unit. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. Integrity has a significant effect on the effectiveness of the work of the Tanjung Enim Regional Technician Implementation Unit employees. The quality of Human Resources has a significant effect on the effectiveness of the work of the Tanjung Enim Market Regional Technician Implementation Unit employees. Work Engagement has a significant effect on the effectiveness of the work of the Tanjung Enim Market Regional Technician Implementation Unit employees. Organizational characteristics have a significant effect on the effectiveness of the work of the Tanjung Enim Regional Technician Implementation Unit employees. Work targets have a significant effect on the effectiveness of the work of the Tanjung Enim Market Regional Technician Implementation Unit employees. Integrity, Quality of Human Resources, Work Engagement, Organizational Characteristics and Work Targets have a significant effect together on the work effectiveness of employees of the Tanjung Enim Market Regional Technician Implementation Unit.